Effect of the order and disorder of BaMoO4 powders in photoluminescent properties - Marques, Ana Paula A.; Picon, Francini C.; Melo, Dulce M. A.; Pizani, Paulo S.; Leite, Edson R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer/plenum Publishers, 2008)
The study of the photoluminescent properties affected by order and disorder of the BaMoO4 powders is the principal objective in this work. BaMoO4 compounds were prepared using soft chemical process called Complex Polymerization Method. In this work, different deagglomeration types and different heating rates were used to promote different disorder degrees. Scheelite type phase (BaMoO4) was determined by X-ray Diffraction (XRD), Fourier Transformed Infra-Red (FTIR) and Raman spectroscopy after heat treating the sample at 400 degrees C. The room temperature luminescence spectra revealed an intense single-emission band in the visible region. Based on XRD and Raman data it was observed that the transition between the completely disordered structure to completely ordered structure is a good condition for photoluminescence (PL) emission. The best PL emission is obtained when the material possesses short range disorder, i.e., is periodically ordered (XRD), but some disorder as measured by Raman spectroscopy. The excellent optical properties observed for disordered BaMoO4 suggested that this material is a highly promising candidate for optical applications.
Keywords: BaMoO4; structural order-disorder; complex polymerization method; photoluminescence